Essential biochemistry - Pratt, Charlotte W.; Cornely, Kathleen (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2013)
Appreciating the structures and functions of biological molecules requires more than looking at pictures or reading about them. This book is designed not only to present information but also to help students develop the ability to answer questions, creating opportunities for them to explore and discover all aspects of biochemistry --Book Jacket.
Previous ed.: 2011.
Includes bibliographical references and index.
Keywords: Biochemistry; Biochemistry